2011
DOI: 10.1002/jmri.22621
|View full text |Cite
|
Sign up to set email alerts
|

Impact of magnetic resonance imaging on cardiac mortality in thalassemia major

Abstract: Purpose:To evaluate whether the introduction of magnetic resonance imaging (MRI) in the management of thalassemia major (TM) patients has affected the risk of cardiac death.Materials and Methods:In all, 804 TM patients from two large reference units were included and the risk of dying of cardiac causes, before and after their first MRI, was assessed by a Cox proportional hazards model with time‐dependent covariates.Results:Adding information from MRI reduced the risk of cardiac death from 6.0 deaths/1000 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 20 publications
(23 reference statements)
0
31
0
Order By: Relevance
“…Since several studies showed a remarkably strong correlation of heart T2* value with clinical cardiac complications, including heart failure and arrhythmia, CMR T2* had been applied to monitor cardiac iron deposition in TM patients in UK [63,64] . Interestingly, the mortality rate was significantly reduced.…”
Section: Cross Sectionalmentioning
confidence: 99%
“…Since several studies showed a remarkably strong correlation of heart T2* value with clinical cardiac complications, including heart failure and arrhythmia, CMR T2* had been applied to monitor cardiac iron deposition in TM patients in UK [63,64] . Interestingly, the mortality rate was significantly reduced.…”
Section: Cross Sectionalmentioning
confidence: 99%
“…Liver R2 magnetic resonance imaging (MRI) has almost completely replaced invasive biopsy for the assessment of liver iron in patients with thalassemia in the United States, and in parallel, liver iron concentration (LIC) has significantly improved in this patient population over the past decade . Cardiac T2* MRI, which enables accurate prediction of the risk of developing iron‐related cardiac disease, is increasingly utilized to tailor iron chelation treatment in patients with thalassemia, and is a factor contributing to improved survival in this patient population . Finally, the availability of oral treatment options, including deferasirox and deferiprone, may improve adherence and control of iron burden compared to subcutaneous infusion with deferoxamine.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the management of cardiac complications have led to a longer life expectancy in patients with transfusion-dependent anemias, 29,30 and other complications, including those related to liver iron overload, are increasingly being seen as a cause of death. 31,32 Therefore, the rapid and clinically significant decrease in liver iron burden from severe levels at baseline in HYPERION is important.…”
mentioning
confidence: 99%